2012
DOI: 10.1038/ncomms1975
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic screen reveals Fbw7 as a modulator of the NF-κB pathway

Abstract: Fbw7 is a ubiquitin-ligase that targets several oncoproteins for proteolysis, but the full range of Fbw7 substrates is not known. Here we show that by performing quantitative proteomics combined with degron motif searches, we effectively screened for a more complete set of Fbw7 targets. We identify 89 putative Fbw7 substrates, including several disease-associated proteins. The transcription factor NF-κB2 (p100/p52) is one of the candidate Fbw7 substrates. We show that Fbw7 interacts with p100 via a conserved d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 46 publications
(70 reference statements)
6
70
0
Order By: Relevance
“…SCF Fbw7 has been shown to target a number of important cellular regulatory proteins for ubiquitylation and proteasomal degradation. These include, among others, cyclins E1 (31)(32)(33) and E2 (34), c-myc (35)(36)(37), c-Jun, SREBP (38), PGC1-␣ (39), Notch (40,41), myeloid cell leukemia 1 (Mcl-1) (42,43), and NF-B2 (44)(45)(46). Since several of these proteins are oncoproteins, it is not surprising that Fbw7 has been found to be mutated in a broad spectrum of human cancers and is therefore considered a tumor suppressor (47,48).…”
mentioning
confidence: 99%
“…SCF Fbw7 has been shown to target a number of important cellular regulatory proteins for ubiquitylation and proteasomal degradation. These include, among others, cyclins E1 (31)(32)(33) and E2 (34), c-myc (35)(36)(37), c-Jun, SREBP (38), PGC1-␣ (39), Notch (40,41), myeloid cell leukemia 1 (Mcl-1) (42,43), and NF-B2 (44)(45)(46). Since several of these proteins are oncoproteins, it is not surprising that Fbw7 has been found to be mutated in a broad spectrum of human cancers and is therefore considered a tumor suppressor (47,48).…”
mentioning
confidence: 99%
“…Recent developments in methods and instruments for mass spectrometry enable quantitative proteomics analysis of complex samples with good coverage (1)(2)(3)(4). Several techniques for quantification by mass spectrometry exist, both using isotopic labeling and label free methods (5,6).…”
mentioning
confidence: 99%
“…Our own work, in collaboration with Sangfelt's laboratory, has shown that FBW7 interacts directly with p100 via a conserved degron and that it promotes degradation of p100 through the GSK3β in phosphorylation-dependent manner. This interaction also affects the complex between the active form of p100, p52, and RelB, which consequently changes the apoptotic balance in the cell 30 . However, what is the contribution of FBW7-mediated regulation of NF-κB towards the regulation of HIF-1α is not yet known.…”
Section: Hif and Nf-κb Functional Crosstalk Shared Targets And Activmentioning
confidence: 99%